BASEL AND RUSSIAN BANKING SYSTEM: PROBLEMS OF IMPLEMENTATION - K. R. Kakhrimanova (Модернизация, инновация, развитие, 2015)
The article contains the refined analysis of the problems of implementation of Basel II and Basel III. Special attention in the article is devoted to significant aspects which should be taken into account in the process of reforming Russian system of banking supervision and regulation in accordance with Basel principles.